The Influence of The Critical Thinking Approach on The Doomsday Faith Material on the Attitude of Hubblullah (Love of God) For Grade IX Students of SMP Pustek Serpong Kota Tangsel In 2023 - Zaimuddin Zaimuddin; Abdul Mu'ti; Aa Saprudin (Jurnal Indonesia Sosial Teknologi, 2024)
Indoctrinative learning approaches are still widely used by PAI teachers. According to Aceng Kosasih, PAI material is static-dogmatic in nature, especially material related to faith, so that learning that is oriented towards critical thinking is irrelevant. The material on faith until the day it ends, for example, is the lecture method that dominates it. This is very impressive considering that religious material should not only express beliefs without a true rationale. On the other hand, the learning approach can function as a tool to understand the material without changing the principles of the faith. The aim of this research is to try to develop a learning approach based on critical thinking in fostering understanding of the material on faith until the Day of Judgment and testing its effectiveness in improving the hubbullah attitude of class IX junior high school students. This type of research is a pre-experimental model with data collection techniques such as interviews, observation, documentation and tests. The data analysis technique used for qualitative data is the Miles and Huberman model, while for quantitative data the Paired Sample T Test is used which is equipped with an N-Gain calculation to see the level of increase in hubbullah's attitude. The results of the application can be taught very well and are representative in increasing understanding and fostering students' hubbullah attitudes. This can be seen from the PAI teacher assessment showing a percentage of 100%. The influence of the critical thinking approach can be observed from the results of the Paired Sample T test with a significance value of 0.000 < 0.05 with a comparison value of 7.754 > 2.042 ttab which means H0 is rejected and Ha is accepted. Regarding the increase in hubbullah's attitude, it can be seen from the calculation of N-Gain = 0.35 with the improvement category being "medium"